Pola Perilaku Konsumsi Islam Karyawan di Yayasan Waqaf Ar Risalah Sumatera Barat - Afriyanti, Afriyanti (Risalah Iqtishadiyah, 2023)
This study aims to determine the extent to which the behaviors of Waqaf Ar Risalah Foundation employees in West Sumatera apply Islamic consumption patterns. Islamic consumption behavior patterns are measured by the values, principles and norms and ethics of consumption in Islam. The pattern of Islamic consumption behavior is a form of consumption by a Muslim that is not only to meet physical needs, but also to meet spiritual need so that in consumption behavior, a Muslim always shows his Islamic law. The main research method used was descriptive qualitative. The research sample was determined as many as 150 respondents. The data collection used was a documentation study, in-depth interviews. Analysis was carried out by narrating the results of the interviews which were then reprocessed by the author. The research results show that there are differences in consumption behavior patterns of employees in terms of income levels and the number of dependents before and after there is one family member who tends to be consumptive which is not fully in accordance with Islamic consumption behavior. This research is expected to provide benefits for Waqaf Ar Risale Foundation employees as learning material so that they continue to pay attention to elements of Islamic consumption in their daily lives.